Citizens’ budget and local community: an insight from Czestochowa - Ślusarczyk, Beata; Herbuś, Aneta (Penerbit Universiti Kebangsaan Malaysia, 2020)
Participatory budget (citizens’ budget) is a relatively new tool used in municipalities to activate the local community. It allows citizens to be involved in the direct decision-making process. These decisions concern mainly the division of budget funds into the most beneficial tasks from the point of view of social development. Citizens’ budget should be fitted to each local government unit, and then be executed in accordance with the previously defined implementation scheme. The aim of the study is to indicate the advantages of using citizens’ budget both from the point of view of local government authorities and individual citizens in Częstochowa. Częstochowa, as the leader of citizens’ budget, is recognizing the residents’ contribution as a co-deciding unit for the distribution of budget funds. It has been using this tool for several years to strengthen social relations. In order to confirm the essence of the participatory budget, in terms of proper relations between local authorities and citizens, the study was carried out a detailed analysis of documents obtained from the City Hall of Częstochowa and professional reports devoted to this subject. The most important advantages pointed out in the use of a participatory budget are social integration, transparency, citizens' identification with the specific territory, increase in the level of trust among citizens and good citizen-official relationship. The study also presents individual formal steps, which need to be taken to introduce the examined phenomenon in a local government unit.